Adherence to the Mediterranean diet and body composition of breast-feeding mothers: the potential role of unsaturated fatty acids. (13th August 2021) - Tabasso, Chiara; Mallardi, Domenica; Corti, Ylenia; Perrone, Michela; Piemontese, Pasqua; Liotto, Nadia; Menis, Camilla; Roggero, Paola; Mosca, Fabio
Abstract: A paucity of evidence is available regarding the impact of diet's quality during pregnancy and lactation on the body composition of breast-feeding mothers. The purpose of the present study was to evaluate the association between maternal degree of adherence to the Mediterranean diet (MD) and body composition measures specifically those relating to body fat, in the lactation period. A cross-sectional study on healthy mothers of full-term babies has been conducted. At 30 ± 10 d after delivery, anthropometric measurements and body composition were assessed. A food frequency questionnaire was performed to compute the Italian Mediterranean Index (IMI) score as an index of adherence to the MD. Data related to pregnancy such as pre-pregnancy weight, gestational weight gain and morbidities were also collected. The 147 mothers included were categorised in IMI-1 (IMI score < 5; n 92) and IMI-2 (IMI score ≥ 5; n 55) groups. IMI-2 mothers showed higher daily energy, total carbohydrates, starch and fibre intakes than IMI-1. The dietary habits of IMI-2 mothers reflect the typical characteristics of MD: they consumed higher quantities of proteins and lipids of vegetal origin, higher amounts of monounsaturated and polyunsaturated fatty acids (PUFAs) and lower saturated to PUFAs ratio. The IMI-2 group showed lower absolute fat mass and fat mass index compared to IMI-1 [(20⋅2 ± 5⋅9) v . (22⋅9 ± 8⋅4) kg; P 0⋅036 and (7⋅5 ± 2⋅2) v . (8⋅5 ± 3⋅1) kg/m 2 ; P 0⋅036, respectively], whereas body weight [(61⋅1 ± 8⋅0) v . (63⋅3 ± 9⋅2) kg] and body mass index [(22⋅4 ± 2⋅6) v . (23⋅3 ± 3⋅5) kg/m 2 ] were similar. The degree of adherence to the MD during pregnancy and lactation is positively associated with lower maternal fat deposition in the breast-feeding period. The higher quality of dietary lipids, probably in synergy with the assumption of starchy carbohydrates and fibre, could influence maternal body fat.